The effect of upper body sprint interval training on golf drive performance - Williams, A. K.; Glen, J.; Sorbie, G. G. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: Improving golf fitness is one way to improve club head velocity and subsequently golf performance. The purpose of the study was to investigate the effect of a three-week upper-body sprint training (SIT) program on power output and golf performance. METHODS: Eleven golfers (handicap: 5.5±2.8) completed the SIT intervention. This was a self-controlled experiment with three testing points (pre-control, post-control and post-intervention) where subjects completed a ballistic bench press, upper-body Wingate and golf testing session. RESULTS: Significant improvements were observed (13.3-15.5%) in peak and mean power production during the Wingate post-intervention in comparison to pre- and post-control time points (P<0.05). This was replicated in peak power for the ballistic bench press for both peak power (P<0.05), but significance for mean power was only observed between post-control and post-intervention (P<0.05) (improvements of 6.1-8.5%). These improvements were not seen consistently in golf performance variables measured, with no significance identified for the 7-iron and significant improvements (P<0.05) observed in Carry Distance (2.2%) and Ball Velocity (1.4%) between pre-control and post-intervention. CONCLUSIONS: Lack of golf performance improvements could be because of the natural variation in club-head velocity across sessions or the inability of subjects to utilise their power gains during the golf swing. Longer SIT interventions may be needed to observe improvements in golf performance.